Peningkatan Hasil Belajar Berpidato Persuasif Melalui Model Discovery Learning Pada Peserta Didik Kelas IX B MTs Miftahul Huda Jleper Kecamatan Mijen Kabupaten Demak - Noor Anisah S.Pd (Jurnal Edutrained : Jurnal Pendidikan dan Pelatihan, 2022)
This study aims to determine the application of the Discovery Learning model for students of class IX B Miftahul HudaJleperin the 2021/2022 academic year to student learning outcomes and determine the effect of the Discovery Learning model on the learning outcomes of students in class IX B Miftahul Huda Jleper in the 2021/2022 academic year. They study used a sample in class IX B which consisted of 34 student . The results of daily assessment learning in Indonesian language learning with persuasive speech text material in class IX B MTs Miftahul Huda Jleper for the 2021/2022 school year show that students get the predÃcate D (29%), C (26%) , B (32%), and A (12%). While the learning outcomes after applying the Discovery Learning model were C (24%),B (44%), and A (32%). The results of the research that have been carried out have conclude the domains of knowledge,attitudes,and skills. Students of MTs Miftahul Huda in the 2021/2022 academic year haveincreased with the application of the Discovery Learning model.